Assessing the mental status of the older person - Rabins, Peter V.; Whiteford-Cohen (Firm); University of Maryland at Baltimore (Baltimore, MD : Video Press, University of Maryland at Baltimore, 1990)
(Producer) Dr. Rabins emphasizes the geriatric patient assessment should include an objective assessment of cognitive function. This assessment can identify problem areas and provide information which can show improvement or decline. This video program provides the unique opportunity to observe Dr. Rabins interacting with normal elders and with dementia patients. Patients interviewed range from normal to severly impaired. Behaviors documented include confussion, loss of memory, hallucination, loss of cognitive skills and depression. This program provides a useful guide on how to do a mental status exam
Peter Rabins
Issued also as a 3/4 in. videocassette
Keywords: Mental health; Neurologic examination; Psychiatric Status Rating Scales; Aged